Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s12967-023-03918-w
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of HMGB1 in tumor-associated macrophages induced by tumor cell-derived lactate further promotes colorectal cancer progression

Abstract: Background Lactate accumulation leads to an acidic tumor microenvironment (TME), in turn promoting colorectal cancer (CRC) progression. Tumor-associated macrophages (TAMs) are the predominant cells in TME. This study aimed to reveal the regulation mechanism of CRC cell-derived lactate on TAMs and explore the mechanism underlying lactate accumulation-induced aggravation in CRC. Methods Cell growth and metastasis were evaluated by colony formation, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…To gain deeper insights into the mechanism of lactate-induced signaling through GPR65 on TAMs and its role in enhancing the malignant progression of glioma, we analyzed six potential cytokines and chemokines (CCL2, CCL5, CCL17, CCL18, HMGB1, and TGFB1) derived from TAMs, which were previously reported to be associated with lactate levels or pro-tumorigenic activities [ 14 , 15 , 18 , 33 , 40 ]. We found that the levels of HMGB1 was obviously elevated under lactate stimulation, which were also dropped down when GPR65 on TAMs was silenced (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To gain deeper insights into the mechanism of lactate-induced signaling through GPR65 on TAMs and its role in enhancing the malignant progression of glioma, we analyzed six potential cytokines and chemokines (CCL2, CCL5, CCL17, CCL18, HMGB1, and TGFB1) derived from TAMs, which were previously reported to be associated with lactate levels or pro-tumorigenic activities [ 14 , 15 , 18 , 33 , 40 ]. We found that the levels of HMGB1 was obviously elevated under lactate stimulation, which were also dropped down when GPR65 on TAMs was silenced (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we found that GPR65 + TAMs could affect the secretion of HMGB1, thereby facilitating the progression and mesenchymal transition of glioma cells. Corresponding to this, HMGB1 also could promote tumor progression in colorectal cancer by activating EMT, Wnt, and ERK signal pathway [ 14 ]. In our study, we found that GPR65 sensing lactate-stimulating promotes the expression and secretion of HMGB1 through cAMP/PKA/CREB pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lactate created by tumor glycolysis forms an acidic tumor microenvironment, under which TAMs are mostly differentiated into M2 type, often exhibiting effects such as promoting tumor cell growth, angiogenesis and cell metastasis 16 . Some studies have revealed that upregulation of HMGB1 in tumor cell‐derived lactic acid‐induced TAMs further stimulated colorectal cancer progression 28 . LncRNA HITT has also been found to diminish lactate creation by reducing PKM2 oligomerization to decline tumor growth and macrophage polarization 29 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been found to boost angiogenesis and provide oxygen and glucose to cancer cells, which in turn facilitates the growth, invasion, and migration of colon cells [ 169 ]. The lactate metabolized by cancerous cells exacerbates CRC progression by prompting macrophages to exhibit M2-type polarization and the production of high-mobility group box 1 (HMGB1), which is essential in maintaining nucleosome structure and controlling the transcription of many genes [ 170 ]. In addition, the accumulation of lactate in the TME creates an acidic environment that impairs the cytotoxic and effector capabilities of T cells, thus enabling tumors to escape the immune system and reducing the effectiveness of certain chemotherapy drugs, all of which have a detrimental influence on CRC prognosis [ 152 ].…”
Section: Obesity-associated Alterations In the Gut Microbiome That Ma...mentioning
confidence: 99%